Menuju Bank Syariah : Demografi Nasabah Dalam Pemilihan Bank - Pandu, Muhammad; Nuraini (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2024)
Apart from management, sharia banks also need to pay more attention to customer characteristics, especially customer criteria in choosing sharia banking services. This is an important issue that needs to be explored by Islamic banks, especially to attract customers from traditional banks which face intense competition. In the banking sector, competition between banks must be effective in order to be successful. Banks with high profitability have high market power. In other words, customers are very important for the success of a bank, including sharia banks. The aim of this research is to determine the influence of respondents' demographic characteristics on their desire to become sharia bank customers. Gender, age, education level, place of residence and expenses are the demographic variables of respondents who are research subjects. The results of this research indicate that expenditure is the most influential factor influencing the intention to become a sharia bank customer. The results obtained from respondents who were not sharia banking customers showed that the main reason for not becoming customers was a lack of information about the advantages of sharia banking products. The results of this research reveal other facts. Based on the correlation results, it is known that the expenditure variable is the main factor that influences the intention to become a Sharia Bank customer. Based on the findings of this research, the first recommendation for Islamic banks is to increase advertising to increase public awareness of the services they provide